Detection and Characterization of Virulent Pseudomonas aeruginosa genes in Fresh Fish at Al-Diwaniya City Market, Iraq. - Ban Ali. Hassan,; Aseel abdulridha saeed (مجلة الانبار للعلوم البيطرية)
Fish meat is more susceptible to pathogen contamination than other protein-rich foodstuffs due to its high deterioration. Pseudomonas aeruginosa is considered one of the most common microbial strains responsible for the deterioration of fish and seafood products. the study's goals are to detecting virulence variables Pseudomonas aeruginosa and estimating the level of contamination in a fish sample, In this research, 120 fresh fish samples, gathered from a the local Diwaniyah city market local fish meat sample. including (60 marine fish and 60 common carp (Cyprinus carpio). The isolates were subjected to numerous biochemical, microbiological, and molecular analyses, and the results showed that about 26 samples were contaminated with Pseudomonas spp. performed on 21.6% of the total sample. Polymerase chain reaction (PCR) was used to amplify 539 bp, 511 bp, and 495 bp, for 16S DNA, Tox A, and Tox S respectively. A total of 21 Tox A genes were identified in 26 P. aeruginosa isolates, whereas the ToxS gene was detected in 17 of the same isolates. According to the results Pseudomonas aeruginosa isolated from fish samples contains multiple virulence factor genes, indicating high pathogenicity, which may affect consumer health because these variants exhibit the capability to increase the pathogenesis of the microorganisms with the severity of the infection and cause economic losses